2018
DOI: 10.5539/jas.v10n10p333
|View full text |Cite
|
Sign up to set email alerts
|

Environment Stratification in the Evaluation of Corn Hybrids in Southern Brazil

Abstract: The implementation of a network of maize trials is an onerous task, so breeding programs seek to eliminate redundant environments, remaining only contrasting ones. The objective was to perform the homogeneous environment grouping by studying the G×E interaction through different environmental stratification methods, as well as to compare the efficiency of these methods. Four methods were used: environmental dissimilarity (Djj); Decomposition of the genotype × environment interaction (G&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…According to Gorgulho and Miranda Filho (2001), the height and the insertion of the ear are highly dependent on the characteristics of the genotypes and growing environments. Plant height is determined genetically Nardino et al, 2018), influenced by plant population (Brachtvogel et al, 2012) and soil nutrient availability (Paterniani, 1997;Cortez et al, 2009;Repke et al, 2013). The EHE varied according to the genotype and growing environment; for Pelotas there was superiority for the PL1, PL2, HP1, HP2 and HP3 genotypes, in contrast, Entre-Ijuís showed higher magnitudes for this character through the PL1, HP3, PL2, HP2 and HC2 genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gorgulho and Miranda Filho (2001), the height and the insertion of the ear are highly dependent on the characteristics of the genotypes and growing environments. Plant height is determined genetically Nardino et al, 2018), influenced by plant population (Brachtvogel et al, 2012) and soil nutrient availability (Paterniani, 1997;Cortez et al, 2009;Repke et al, 2013). The EHE varied according to the genotype and growing environment; for Pelotas there was superiority for the PL1, PL2, HP1, HP2 and HP3 genotypes, in contrast, Entre-Ijuís showed higher magnitudes for this character through the PL1, HP3, PL2, HP2 and HC2 genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…This character is of extreme importance for the crop, since it is determinant for the best balance of the plant (Kappes et al, 2011;Nardino et al, 2016b). Research has shown that this characteristic can be influenced by the intraspecific competition of plants per unit area (Kappes et al, 2011;Nardino et al, 2016c), high levels of nitrogen fertilizers (Santos et al, 2010), potassic fertilizers (Rodrigues et al, 2014), and characteristics of the genotype used (Meira, 2006). Studies have determined that 83% of modern corn genotypes show a height of spike insertion of around 1.3 m (Sawazaki & Paterniani, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Detasseling is done prior to full maturity of anthers, when the tassel has emerged out of the leaf sheath. Detasseling is approached very carefully, it is performed either manually with a skilled labor [3,4], since the base of the tassel is not visible, or mechanically. With more intensive defoliation, there is greater certainty that the entire tassel would be removed.…”
Section: Introductionmentioning
confidence: 99%